Insights Into Sibling Relationships and Longevity From Genetics of Healthy Ageing Nonagenarians: The Importance of Optimisation, Resilience and Social Networks - Rea, Jennifer Nicola M.; Broczek, Katarzyna Milana; Cevenini, Elisa; Celani, Laura; Rea, Susanne Alexandra J.; Sikora, Ewa; Franceschi, Claudio; Fortunati, Vita; Rea, Irene Maeve (Frontiers in Psychology, 2022)
Understanding how to ‘Age Longer and Age Well’ is a priority for people personally, for populations and for government policy. Approximately ten percent of nonagenarians reach 90 years and beyond in good condition and seem to have a combination of both age-span and health-span. However, the factors which contribute to human longevity remain challenging. Culture is a shared system of learning ideas, feelings, and survival strategies. It has a strong influence on each person’s psychological development, behaviour, values and beliefs. Nonagenarians have rich life experiences that can teach us much about ageing well; they are rich reservoirs of genetic, lifestyle and psychological information which can help understanding about how to live longer and better. Sibling or trio nonagenarians are important sources of family beliefs and behaviours upon which individual personalities may have been built. Their personal family histories and narratives are powerful tools that help to determine familial traits, beliefs and social behaviours that may help establish factors important in the siblings’ longevity. Using purposefully selected subjects, recruited to the Genetics of Healthy Ageing (GeHA) project in four European countries, this research used the simple life story and qualitative research methods to analyse contrasting and distinctive questions about the interface between the psychological and social worlds in the nonagenarian siblings’ insights about their longevity. Their stories aimed to give better understanding about which psychological aspects of their common life journey and the degree of emotional support in their sibling relationships have supported their paths to longevity. The most universal finding in each of the four European countries was that nonagenarians demonstrated high positivity, resilience and coping skills and were supported in social networks. Around this theme, nonagenarians reported ‘being happy’, ‘always cheerful’, ‘never melancholy’ and having a contentment with a ‘rich life’ and family relationships which fits with accumulating evidence that life satisfaction comes from a perceived self-efficacy and optimism. Most sibling relationships in this study, when analysed according to the Gold classification, fit the ‘congenial’ or ‘loyal’ relationship type – demonstrating a healthy respect for the others’ opinion without overt dependence, which may help individual coping and survival mechanisms.